Explainable autonomous robots: a survey and perspective. (19th March 2022) - Sakai, Tatsuya; Nagai, Takayuki
Abstract : Advanced communication protocols are critical for the coexistence of autonomous robots and humans. Thus, the development of explanatory capabilities in robots is an urgent first step toward realizing autonomous robots. This survey provides an overview of the various types of 'explainability' discussed in the machine learning literature. The definition of 'explainability' in the context of autonomous robots is then discussed by exploring the question: 'What is an explanation?' We further conduct a survey based on this definition and present relevant topics for future research in this paper. GRAPHICAL ABSTRACT: UF0001